Running periodization (part 3 - block & undulating periodization) - Karp, J. (Techniques Magazine, 2023)
In addition to linear and reverse linear periodization, the subjects of the first two parts of this series, there are a couple other ways to plan your athlete´s training. This article talks about block periodization and undulating periodization.